Molecular evolution during dynamic vulcanization of polyolefin mixtures for lead‐free thermoplastic vulcanized. (12th December 2019) - Ciardelli, Francesco; Dossi, Stefano; Galanti, Andrea; Magri, Andrea; Riolo, Stefano
Abstract : The preparation process and the final properties of new thermoplastic lead‐free medium voltage (MV) insulation compounds based on the thermoplastic vulcanized (TPV) technology are reported and discussed at molecular level. The TPV MV insulation compounds were prepared starting from a peroxide curable lead free MV insulation, which is the actual market benchmark. For this reason, they were extensively investigated in comparison to the standard lead free MV insulation. The results of the dynamic vulcanization process were evaluated and related to the formulation. Now in the present paper we are reporting a detailed analysis of the molecular changes induced by the vulcanization reaction with reference to the different polymers and low molecular weight additives present in the starting mixture. The results are analyzed with reference to the used polyolefins structure with the aim to provide insights helping to relate the formulation at molecular level to the behavior of the final complex materials thus offering an useful tool to a priori design of TPVs with the desired ultimate properties.